Proposta pedagógica para o ensino médio do estado do Rio Grande do Sul - gestão 2011/2014 - e sua relação com a educação física e o mundo do trabalho - Ramos, Fabrício Krusche (2015)
This study of the pedagogical proposal to the Polytechnic High School and Professional Education Integrated with State High School of Rio Grande do Sul-management 2011/2014. We analyze the characteristics of the changes of the proposal and its implications for the teaching of physical education. For this we use the theoretical basis of Dialectical Materialism History and as technical research documentary and bibliographical analysis. We followed a path that allowed us to view the Concrete-Abstract-Concrete triad where the First Chapter - Concrete - present a pedagogical proposal for the High School of Rio Grande do Sul State - Management 2011/2014, through preliminary approaches; In the Second Chapter - Abstract - we perform bibliographical analysis relating to labor categories and Education, Labor and Education Principle, Polytechnic; Physical Education. In the Third Chapter - Concrete - present the final synthesis, the Pedagogical Proposal for the High School of Rio Grande do Sul State - Management 2011/2014, and its implications for the teaching of physical education. We emphasize that these final summaries are presented also our final remarks. We synthesize, that in order to keep up with changes in the workplace, the school also restructures, as there is a need for there to guarantee that the transmission of flexible skills enable individuals to fight for the few places available in the labor market . In this scenario, it is up to education to ensure that the development of skills to ensure learning throughout life, and it is configured as a major category in the pedagogy of flexible accumulation. Configured so it is up to the regular market the paths to be followed by education, meeting the short-term capital interests. In this process, the current reform in EM is based on the parameters of international organizations, in that it maintains that the ability to make passes to be replaced by intellectualization of skills requiring formal logical reasoning, the field of forms of communication, flexibility to change, ability to learn permanently and resistance to stress and in the defense of work as an educational principle and the polytechnic, contributes strongly to materialize this logic. The teaching of EF while polytechnic and taking work as an educational principle, but adapted to new settings required by the labor market, is based on evaluative experiences that have content for students and within the pedagogy of logic skills, their own experiences They stand out against the other knowledge, thus gaining a dimension that goes beyond its own limits and, if so, lacking a mediation with the scientific and elaborate knowledge. Again, EF, through changes to its content and its methodological formulation, chooses to contribute to the formation of a perfectly adaptable to the system logic worker.